Quality control in integrated navigation systems - Teunissen, Peter (1990)
Real-time estimation of parameters in dynamic systems becomes increasingly important in the field of high precision navigation. The real-time estimation inevitably requires real-time testing of the models underlying the navigation system. This paper presents: 1. A real-time recursive testing procedure that can be used in conjunction with the well-known Kalman filter algorithm: 2. Diagnostic tools for inferring the detectability of particular model errors. The testing procedure consists of three steps: detection, identification and adaptation. It can accomodate model errors in both the measurement model and dynamic model of the integrated navigation system. The tests proposed are optimal in the uniformly-most-powerful-invariant sense.